Cartilage degeneration of patellofemoral joint occurs in open wedge high tibial osteotomy, rather than in hybrid closed wedge high tibial osteotomy, during the early postoperative period: A qualitative analysis using MRI T2 mapping. (9th February 2023) - Komaki, Shintaro; Nakagawa, Shuji; Arai, Yuji; Inoue, Atsuo; Kaihara, Kenta; Hino, Manabu; Kan, Hiroyuki; Kenji Takahashi
Purpose: After high tibial osteotomy, the patella may change position and osteoarthritis of the patellofemoral joint (PFJ) may occur. It was hypothesized that the course of PFJ degeneration would differ between open wedge high tibial osteotomy (OWHTO) and hybrid closed wedge high tibial osteotomy (hybrid HTO). Accordingly, this study aimed to evaluate the qualitative changes in PFJ articular cartilage, during the early postoperative period after OWHTO and hybrid HTO. Methods: This was a retrospective observational study of 75 knees that underwent OWHTO (N = 37) or hybrid HTO (N = 38) for medial knee osteoarthritis. OWHTO and hybrid HTO were indicated for corrections of less than 10° and more than 10°, respectively. MRI of all knees was performed before and 6 months after surgery to evaluate patellar cartilage in sagittal images for T2 mapping. Three regions of interest (medial, middle, and lateral facets) were defined in the articular cartilage, and T2 values were measured. Patellar tilting angle, lateral shift ratio, and patellar height were compared before and after surgery. Results: There was no significant change in arthroscopic findings of PFJ articular cartilage between the OWHTO and hybrid HTO groups. In the OWHTO group, the mean T2 value of medial and middle facets increased significantly (lateral, 43.0 ± 3.9 to 43.7 ± 3.5; middle, 44.2 ± 3.9 to 46.2 ± 3.8; medial 41.0 ± 4.3 to 42.4 ± 4.0). Conversely, no significant change was observed in the hybrid HTO group (lateral, 41.1 ± 4.0 to 42.3 ± 4.0; middle, 43.6 ± 4.2 to 44.5 ± 4.3; medial, 40.7 ± 4.1 to 41.5 ± 4.5). Patellar height decreased and increased in the OWHTO and hybrid HTO groups, respectively, and patellar tilt decreased in the OWHTO group. Lateral shift ratio decreased significantly in both groups. Conclusions: OWHTO with a small correction angle may result in qualitative changes in PFJ articular cartilage from an early stage, while hybrid HTO with a relatively large correction angle is unlikely to affect PFJ articular cartilage.